The Effect of Leadership and Remuneration on Employee Turnover Intention with Work Culture as a Moderating Variable - Fathonah, Inna Halimatul; Zulganef, Zulganef (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
Transformational leadership has a significant impact on organizations, particularly in motivating employees to drive innovation. In addition, effective leadership greatly influences employee performance. Apart from leadership, remuneration also plays a critical role in employee retention and performance. This research aims to analyze the influence of leadership and remuneration on employee turnover intention with work culture as a moderating variable. The study focuses on employees in the development division of PT TKG Taekwang Indonesia, a multinational footwear manufacturing company located in Subang, West Java. Using a quantitative research method, this study employs a descriptive and verification approach. Data was collected through questionnaires distributed to 87 employees using a saturated sampling technique. The results show that both leadership and remuneration significantly affect turnover intention, while work culture acts as a moderating factor that can either strengthen or weaken these relationships. The findings emphasize the importance of strategic leadership, fair remuneration, and strong work culture in minimizing employee turnover intention and fostering organizational sustainability.